THE INFLUENCE OF STIMULATION OF ORGANISM WITH BACTERIAL LIPOPOLYSACCHARIDE ON THE BACKGROUND OF METABOLIC SYNDROME MODELING ON THE DEVELOPMENT OF OXIDATIVE STRESS IN RAT HEART - Akimov, O.Y.; Mykytenko, A.O.; Kostenko, V.O.; Yeroshenko, G.A. (World of Medicine and Biology, 2023)
Metabolic syndrome is one of the most widespread non-infectious pathologies in the world affecting almost a quarter of world population. The purpose of this work is to determine the activity of antioxidant enzymes, the production of superoxide anion radical, the content of oxidatively modified proteins and the concentration of malondialdehyde in the heart of rats under conditions of experimental metabolic syndrome and stimulation of the organism with bacterial lipopolysaccharide. In the test group of animals superoxide production increased by 6.31 times, activity of superoxide dismutase decreased by 2.97 times, the activity of catalase decreased by 2.4 times, the concentration of malondialdehyde increased by 3.08 times, and the content of oxidatively modified proteins increased by 2.81 times. Stimulation of organism with bacterial lipopolysaccharide on the background of induction of metabolic syndrome by high fructose diet shows synergetic effect on increase of reactive oxygen species production, severely decreases activity of antioxidant enzymes and intensifies oxidative damage to protein and lipid structures of rat heart.